Report from a symposium on accelerating policy-driven action against excessive sugar consumption for the prevention of early childhood caries and noncommunicable diseases - Om P Kharbanda; Paula Moynihan; Harsh Priya; Anupama Ivaturi; Arpit Gupta; Desmia Haldane (Wolters Kluwer Medknow Publications, 2018)
Dental diseases and other noncommunicable diseases (NCDs) share common risks. Omnipresent and easily available sugars are a contributing risk factor for overweight, obesity, and diabetes. In addition, sugar consumption is known to cause dental caries in early childhood (early childhood caries) and in adults. It has been noticed that the prevalence of NCDs is increasing each year, leading to 70% of deaths. A symposium of diverse academicians was convened to identify the gaps in evidence, policy, and advocacy for action on sugars, emphasizing on its detrimental effects on oral health. Existence of policies on sugars, experiences of other countries, feasibility in India, and the role of public health dentists, public, and stakeholders were discussed. Policy priorities in India and advocacy to strengthen action against inappropriate sugar intake could help address the growing burden of sugar-related NCDs. Recommendations to this end were put forth by the panel of experts.